2010
DOI: 10.1016/j.beth.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Specific Phobia in Youth: Phenomenology and Psychological Characteristics

Abstract: Sociodemographic and psychological characteristics of 62 youth with animal and natural environment types of specific phobia were examined in a treatment-seeking sample. Differences due to age, sex, ethnicity, family structure, and family socioeconomic status were not found between youth with the two types of specific phobia. Moreover, differences were not obtained between the two groups in the clinical severity of their phobias, the perceived dangerousness of the feared outcomes associated with their phobias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 30 publications
1
22
0
5
Order By: Relevance
“…[23] However, another study with adults showed that whereas both animal phobia and natural environment phobia were associated with impairment as measured by seeking professional help, interference with daily life, and interference with social functioning, situational phobia and B-I-I phobia were found to be more significantly impairing than either animal phobia or natural environment phobia. [6] Still, another study found no differences in impairment among different types of SP (measured by the F-DIPS, Diagnostic Interview for Psychiatric Disorders-Research Version) among different SP types.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[23] However, another study with adults showed that whereas both animal phobia and natural environment phobia were associated with impairment as measured by seeking professional help, interference with daily life, and interference with social functioning, situational phobia and B-I-I phobia were found to be more significantly impairing than either animal phobia or natural environment phobia. [6] Still, another study found no differences in impairment among different types of SP (measured by the F-DIPS, Diagnostic Interview for Psychiatric Disorders-Research Version) among different SP types.…”
Section: Resultsmentioning
confidence: 96%
“…[4] In a sample of clinic-referred children and adolescents, youth with natural environment phobias (primarily storms and dark/alone) were found to have more somatic/anxious symptoms and depressive symptoms than youth with animal phobias. [23] Youth with the natural environment type also had higher rates of comorbidity with other anxiety disorders, including generalized anxiety disorder (GAD) and separation anxiety disorder.…”
Section: Resultsmentioning
confidence: 99%
“…We also reasoned that phobia type might be related to emotional arousal on the BAT, such that there would be more children with the natural environment type in the high arousal-high distress group, more children with the animal type in the low arousal-low distress group, and an equal number of each in the discordant group. This hypothesis was based on recent findings showing that children with natural environment phobias differ from children with animal phobias on somatic/anxious symptoms, depressive symptoms, life satisfaction, and co-occurring anxiety disorders (Ollendick, Raishevich, Davis, Sirbu, & Öst, 2010). We did not offer hypotheses about situational or blood-injury-injection phobia types because we did not have a sufficient number of youth in the former group to examine such hypotheses and the latter group was specifically excluded from the original study from which these participants were drawn (Ollendick et al, 2009).…”
mentioning
confidence: 99%
“…This finding can be explained by the fact that fear in specific phobias is generally bound to one circumscribed stimulus or situation and by definition mainly arises during confrontation with that stimulus or situation (American Psychiatric Association, 2013), whereas fear in the other anxiety disorders tends to be more global and omnipresent in youths' lives. This does not imply, however, that specific phobias should be taken less seriously as research has demonstrated that this type of psychopathology also has a significant negative impact on the daily functioning of children and adolescents (e.g., Ollendick, Raishevich, Davis, Sirbu, & Öst, 2010). Comparisons of the FSSC-R-SF subscale scores across the diagnostic groups revealed that the presence of a major anxiety disorder was accompanied by higher levels of 'fear of failure and criticism', 'fear of the unknown', 'fear of danger and death', and 'medical fears' as compared to youths without such anxiety disorders.…”
Section: Discussionmentioning
confidence: 95%